Queer X design : 50 years of signs, symbols, banners, logos, and graphic art of LGBTQ - Campbell, Andrew Raymond, 1982- (New York : Black Dog & Leventhal Publishers, 2019)
The first-ever illustrated history of the iconic designs, symbols, and graphic art representing more than 5 decades of LGBTQ pride and activism--from the evolution of Gilbert Baker's rainbow flag to the NYC Pride typeface launched in 2017, and beyond. Organized by decade beginning with Pre-Liberation and then spanning the 1970s through the new millennium, QUEER X DESIGN will be an empowering, uplifting, and colorful celebration of the hundreds of graphics--from shapes and symbols to flags and iconic posters--that have stood for the powerful and ever-evolving LGBTQ movement over the last five-plus decades. Included in the collection will be everything from Gilbert Baker's original rainbow flag, ACT-UP's Silence = Death poster, the AIDS quilt, and Keith Haring's "Heritage of Pride" logo, as well as the original Lavender Menace t-shirt design, logos such as "The Pleasure Chest", protest buttons such as "Anita Bryant Sucks Oranges", and so much more. Sidebars throughout will cover important visual groupings such as a "Lexicon of Pride Flags", explaining the now more than a dozen flags that represent segments of the community, and the evolution of the pink triangle.
Introduction -- Pre-Liberation -- 1970s -- 1980s -- 1990s -- 21st Century.
boek
Keywords: Sexual minorities in art -- History; Homosexuality and art -- History; Signs and symbols -- History; Sexual minorities -- History; Universal design -- History